2019
DOI: 10.3390/ijms20194827
|View full text |Cite
|
Sign up to set email alerts
|

Selecting an Appropriate Animal Model of Depression

Abstract: Depression has become one of the most severe psychiatric disorders and endangers the health of living beings all over the world. In order to explore the molecular mechanism that underlies depression, different kinds of animal models of depression are used in laboratory experiments. However, a credible and reasonable animal model that is capable of imitating the pathologic mechanism of depression in mankind has yet to be found, resulting in a barrier to further investigation of depression. Nevertheless, it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 112 publications
1
131
0
2
Order By: Relevance
“…The depletion of catecholamines (norepinephrine, epinephrine, and dopamine) and serotonin (5-HT) leads to morphological changes in the brain of tested animals and has good face validity due to the appearance of the depression-like phenotype [ 145 , 146 , 147 , 148 , 157 ]. This model is widely used in preclinical studies to evaluate the antidepressant effect of new developing drugs and plant compounds [ 149 , 150 , 151 , 152 , 153 , 154 ] due to the short-term time and good predictive validity [ 147 , 155 ]. However, reserpine treatment produces motor impairments mimicking Parkinson disease dyskinesia, increased nociceptive sensitization and hypothermia and has high mortality rate [ 148 , 155 , 156 , 157 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of catecholamines (norepinephrine, epinephrine, and dopamine) and serotonin (5-HT) leads to morphological changes in the brain of tested animals and has good face validity due to the appearance of the depression-like phenotype [ 145 , 146 , 147 , 148 , 157 ]. This model is widely used in preclinical studies to evaluate the antidepressant effect of new developing drugs and plant compounds [ 149 , 150 , 151 , 152 , 153 , 154 ] due to the short-term time and good predictive validity [ 147 , 155 ]. However, reserpine treatment produces motor impairments mimicking Parkinson disease dyskinesia, increased nociceptive sensitization and hypothermia and has high mortality rate [ 148 , 155 , 156 , 157 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…This model is widely used in preclinical studies to evaluate the antidepressant effect of new developing drugs and plant compounds [ 149 , 150 , 151 , 152 , 153 , 154 ] due to the short-term time and good predictive validity [ 147 , 155 ]. However, reserpine treatment produces motor impairments mimicking Parkinson disease dyskinesia, increased nociceptive sensitization and hypothermia and has high mortality rate [ 148 , 155 , 156 , 157 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…The inhibition percentage was calculated according to the Eq. 6 [34][35][36]. Accordingly, mice were gently placed in a transparent Plexiglas cylinder (30 cm height × 20 cm width) filled with water (15 cm from the bottom), set at room temperature (23-25°C).…”
Section: Marble-burying Testmentioning
confidence: 99%
“…Pre-clinical studies conducted on murine model also confirmed this causality. A chronic stress, such as exposure to a long-term inescapable stimulation or a chronic social defeat, is indeed able to induce depressive symptoms in rodents as revealed by specific behavioral tests such as forced swimming test, tail suspension test and sucrose preference test (Hao et al, 2019). Although modeling human depression in animals is challenging and present several limitations, rodent models have been useful in describing specific aspects of mood disturbances in well-designed experimental settings (Hao et al, 2019).…”
Section: Mdd Pathophysiology Hypothesis: the Monoamine Theory And Thementioning
confidence: 99%